Physical Training and Physical Rehabilitation for the Personnel of the Ministry for Emergency Situations under the Condition of High Radiation - Narskin, Геннадий Иванович (Chrezvychaynye situatsii: obrazovanie i nauka, 2006)
The author of the article presents the concept of physical rehabilitation for the personnel of the Ministry for Emergency Situations paying attention to the specific features high-level radiation impact.